Array - Anggraeni, Nina (Paradigma, 2021)
Divorce is basically a break in the marital relationship between husband and wife due to various causes. This research is motivated by the high number of divorce cases which are dominated by the wife's lawsuit. So that the number of single parent males is increasing. This study focuses on the experiences of single parent men in carrying out domestic functions after divorce. This research was conducted in Nglegok Village, Nglegok District, Blitar Regency. The subjects in this study were selected by purposive sampling which included single parent males with an age range of 30 to 45 years and had child custody, and had been divorced for a minimum of two years with a legal divorce background. Data collection techniques were obtained through observations, interviews and documentation.This study uses a qualitative research method with the phenomenological perspective of Edmund Husserl. Edmund Husserl's phenomenological approach looks at the world of each individual's consciousness to find meaning from everyday life experiences. The results show that single parent men have awareness in carrying out domestic functions after divorce. All domestic functions ranging from cooking, cleaning the house to raising children are done independently. As a single parent man, he tries to eliminate a bad image from the community regarding the ability to do work on domestic functions in the postdivorce family. The status of a single parent male interprets it as the duty and responsibility of being the head of the family as well as the head of the household. Keywords : Single Parent Male, Domestic Function, Post Divorce